TAKABBUR DALAM PERSPEKTIF AL-QURAN DAN HADITS - Suhemi, Emi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2019)
This study aims to determine the perception of the Koran about takabbur this research uses descriptive method and uses the maudhu'iy interpretation approach or thematic interpretation which is collecting a number of verses that discuss the concept of takabbur while the selected interpretation book is the interpretation of al-Misbah which represents the work of modern interpretation and Ibn Kathir representing classical interpretations. Knowledge about takabbur is very urgent or important to be known by every Muslim person because in the statement of the Qur'an and al-Hadith it is stated that does not enter heaven when someone dies in his heart is stored in the character of takabbur. The results of the study found that the origin of the nature of this obscurity was initiated by Shaytan who then transformed into human behavior and also found forms of behavior categorized as takabbur behavior such as; walking proudly, talking like a donkey, looking away, looking down on others.